Students exchange programme - Wee, Cindy (Universiti Teknologi MARA, Sarawak, 2004)
A group of 12 American students invaded my BEL 200 class and quickly took their seats. My students were quiet for once and did not know how to react. To make matters worse, the crew from NTV 7 zoomed into the class next. It did not take long to break the ice and everyone was let lose to interact and the atmosphere was transformed into real conversation in English!